Vocational Students' Perception of Online Learning during the Covid-19 Pandemic - Hilma Erliana; Safrizal Safrizal; Rahmad Nuthihar; Luthfi Luthfi; Wahdaniah Wahdaniah; Ilham Jaya; RN Herman (Faculty of Engineering, Universitas Negeri Yogyakarta, 2021)
COVID-19 pandemic impacts on vocational education. Lectures that were originally conducted face-to-face learning are diverted to online learning to avoid the spread of the pandemic. Online learning is very difficult to apply for courses conducted in the laboratory. This study discusses vocational students’ responses to the practice of online learning during the COVID-19 pandemic. Data were collected through a questionnaire created on Google form consisting of 20 questions. The questionnaire used a Likert scale to find out the attitudes and students’ perceptions of the implementation of online learning. The number of research respondents was 107 people consisting of 45 respondents from the West Aceh State Community Academy and 62 respondents from Lhokseumawe State Polytechnic, Aceh, Indonesia. The results of this study found that 59.81% of students disagree with online learning. The results also showed a score of 76.95% of the students agree that internet access is the main obstacle in online learning. However, students’ satisfaction with the current online learning system for students shows a score of 67.50%. Opinions related to online learning from 107 respondents showed that 45.42% of them less agree if online learning is still applied when the COVID-19 pandemic ends.